The impact of chronotype on obesity-related outcomes : diet, behaviour and metabolic health : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Nutritional Sciences at Massey University Auckland, New Zealand - van der Merwe, Carlien (Massey University, 2023)
Background: Describing the effect of the diet on obesity risk as simply excessive energy intake, does not factor in the patterning (spacing, skipping and timing), or format (food combinations and nutrient content) of meals consumed or the specific eating behaviours that contribute to weight gain. In addition to this, chronotype, may also play a role in the complex aetiology of obesity. Being a very late (=evening type, ET) or early chronotype (=morning type, MT) not only determine preferred sleep- and wake-times but may also influence mealtimes, nutritional composition of meals and eating behaviour. This may impact the circadian timing system and in the long-term, result in weight gain, obesity, and poor metabolic function. Aims: To explore the diet in-depth (eating patterns and eating behaviours) as it relates to different chronotypes and metabolic health markers of New Zealand (NZ) European and Pacific women with different body fat profiles and varied metabolic disease risk factors. Methods: This research formed part of the PRedictors linking Obesity and gut Microbiome (PROMIsE) cross-sectional study that was conducted at the Massey University in Auckland, NZ. Healthy women, between the ages of 18 and 45 years were recruited based on healthy BMI (18.5 -24.9 kg/m²) and obese BMI (≥30 kg/m²) within NZ European (n = 162) and Pacific (n = 142) ethnic groups. Chronotype, was assessed using the Munich Chronotype Questionnaire. Fasting venous blood samples were collected to assess metabolic biomarkers (hormones, lipid profile and glucose homeostasis). Anthropometrical measurements included, body mass index (BMI), and whole-body total fat percentage (BF%), android-and gynoid- fat mass were assessed using dual-energy x-ray absorptiometry. Five-day food records were used to assess dietary intake. The Three Factor Eating Questionnaire and the Eating Attitude Test -26 was used to assess eating behaviour and - attitudes. Results: Half of participants were intermediate type (IT; n = 155, 54%) followed by ET (n = 97, 34%) and MT (n = 35, 12%), with most Pacific women being ET (n = 83, 86%) and most NZ Europeans being IT (n = 115, 65%). Due to low sample size, the MT and IT were combined as MT-IT, for some analyses. The MT-IT women had lower BMI, BF% and android to gynoid fat percentage (AG) ratio, lower concentrations of triglycerides, insulin, leptin, LDL-cholesterol, HbA1c and higher HDL-cholesterol and ghrelin in comparison with ET. Total daily energy and macronutrient intakes were similar across the chronotype groups. Women classified as MT-IT vs ET had higher intakes of energy, protein, carbohydrate, and fat in the morning (by 10:00). Conversely at night (after 20:00) the ET had a higher energy, protein, carbohydrate, and fat intake. The ET in the high BF% as well as high AG ratio group predicted lower energy, protein and carbohydrate intakes in the morning, and predicted higher energy, carbohydrate and fat intake at night compared with MT-IT. Women with an earlier chronotype (MT-IT) followed dietary patterns that consisted of high micronutrients, protein, fat and fibre, namely, the Healthy food pattern, Animal Products food pattern and the High Protein-Fat-Fibre nutrient pattern. The ET women followed the High Carbohydrate nutrient pattern high in poor quality carbohydrates. Eating behaviour was associated with chronotype. The ET had higher scores for unfavourable eating behaviours such as lower restraint scores (conscious restriction of food intake to control body weight), while having higher hunger scores in comparison with the MT-IT. In the high BMI group, ET predicted lower restraint, rigid control, but higher perceived hunger, internal locus for hunger, habitual disinhibition (loss of control of food intake) and bulimia & food preoccupation, compared with MT-IT. Conclusion: This PhD thesis found that ET when compared to MT were more likely to have a higher body composition and an unhealthy metabolic biomarker profile. This chronotype-body composition relationship may be linked to the ET’s irregular eating patterns and unhealthy eating behaviours that may contribute to the circadian misalignment. Although the chronotype groups had similar nutrient intakes, clear differences were noticeable regarding the types and combinations of foods consumed together as well as the distribution of food intake throughout the 24-hour day. The ET distributed their nutrient intake towards the night, the circadian phase of the day that is metabolically more suited to fasting in comparison with the MT-IT that had a higher nutrient intake during the morning, the feeding phase of the day. This PhD thesis showed that consuming a higher amount of nutrients in the morning and during the early part of the day, seemed to be protective against developing obesity. These findings give further insight into the differences in eating patterns and eating behaviours between non-obese and obese individuals, placing an individual’s chronotype at the center.
Keywords: Women; Health and hygiene; Sleep-wake cycle; Obesity; Food habits; New Zealand; 321004 Nutritional science